Durability of lithium-ion 18650 cells under random vibration load with respect to the inner cell design. (October 2020) - Berg, Philipp; Spielbauer, Markus; Tillinger, Michael; Merkel, Matthias; Schoenfuss, Maik; Bohlen, Oliver; Jossen, Andreas
Abstract: Lithium-ion batteries undergo random vibrations in automotive applications, for example due to rough road surfaces. So far, no investigation based on random vibration has considered the influence of the inner cell design and the influence of cyclic aging on vibration durability. Therefore, in this study, 18 different 18650 cell types from seven different manufacturers are tested, using two random vibration load profiles. The applied vibration profiles are the random profile according to the standard SAE J2380 and another upscaled, more severe profile. The SAE J2380 test is carried out using both new and electrically pre-cycled cells. All cell types are analyzed by computed tomography in terms of their inner design with a focus on inner mandrel, spacer and tab design. The performance of the cells is checked in terms of capacity, electrochemical impedance spectroscopy and post-vibration computed tomography. None of the cells shows significant electrical performance degradation due to the vibration. Post-vibration computed tomography reveals mechanically damaged negative current collector tabs inside of two cell types due to a loose mandrel in the case of the upscaled profile. These cell types have the lowest ratio of mandrel diameter to inner jelly roll diameter, emphasizing the importance of the inner cell design for vibration durability.